The Relationship between Environment and Income: Regression Spline Approach - Omay, Rabia Ece (International Journal of Energy Economics and Policy, 2013)
This paper examines the relationship between economic growth and carbon dioxide (CO2) emissions, the dominant contributor to the greenhouse effect, in Turkey. For time series data for the period 1980-2009 taking into account the Environmental Kuznets Curve (EKC) was modeling. The results show that there are N-shaped relationship between CO2 emissions and economic growth, so these findings do not support EKC hypothesis with inverted-U shaped curve. At this point, because of the presence of a cubic polynomial, regression spline method is used as a different approach and a new model has been proposed. The model gives better results according to different model selection criteria. Keywords: Environmental Kuznets curve; CO2 emissions; regression spline; thin plate regression spline JEL Classifications: C14; C22; Q53; Q56